Development Of A Digital Platform Prototype For The Sustainable Decision Support System On The Kenaf Fiber Agro-Industry Supply Chain - Nurhasanah, Nunung Nurhasanah; Riyana, Tharra Riyana; Noriko, Nita Noriko; Wibowo, Dhia Wibowo; Ramadanti, Amelia Ramadanti; Haryadi, Dody Haryadi (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2024)
Kenaf plants are able to absorb 21 to 89 tons of CO2 per hectare per year, depending on the agronomic management and environment. Kenaf plant-based fiber agro-industry in Indonesia serves as an upstream industry that has a potential to increase the export value contribution of kenaf dried fiber, while allowing domestic demand for kenaf dried fiber to be met through Indonesian production. This will have an impact on the reduced value of kenaf dried fiber import. The purpose of this study was to develop a digital platform prototype of a sustainable decision support system for kenaf fiber agro-industry supply chains. Development of this digital platform relied on an Android OS with Java language based decision support system framework, which was previously established using a system development life cycle (SDLC), Waterfall model. This research has succeeded in developing a digital platform decision support system for a sustainable kenaf fiber agro-industry supply chain using a waterfall model SDLC approach. This digital platform helps users to make decisions regarding alternative opportunities for cleaner production and increasing green productivity through measuring green productivity indexes with GVSM as the input. This research can be further developed for implementation of intelligent system-based DSS. Therefore, in future research, DSS can be developed with a model-based management system using an intelligent systems approach.